DESIGN CONCEPTS OF AN ONBOARD EARLY WARNING SYSTEM OF PILOT ABOUT ENTERING WAKE VORTICES FROM ANOTHER AIRCRAFT - I. G. Golovnev; V. V. Vyshinsky; A. I. Zhelannikov; K. V. Lapshin (Научный вестник МГТУ ГА, 2018)
An airborne aircraft forms a wake vortex behind itself dangerous for other entering it aircraft both piloted and unmanned. Wake vortex intensity depends on parameters of the aircraft creating it, so the greater the aircraft mass is, the higher its impact on other aircraft is. It is not possible to register visually the wake vortex, since in fact it is invisible. Introduction of wide-body aircraft like A380 into service leads to the revision of separation rules with the aim to increase admissible distance between aircraft. There is a quite demonstrative case when Challenger 604 got into the wake vortex after A380: though separation rules at the altitude were observed, Challenger performed an out-of-control rotating descent from the altitude of 10000 m to 3000 m. At present, in spite of multi-year research there are no real verified suggestions on wake vortex safety of aircraft flights. The paper presents the methodological basis and design concepts of an onboard early warning system of a pilot about entering wake vortices from another aircraft. The main task of the proposed system is to reveal wake vortices according to pressure decrease in their cores; to do it we perform on-line measuring of pressure in front of an aircraft. Measurements are done by a standard onboard air data system and an onboard inertial satellite system in order to control the consistency of “barometric” altitude readings and those of altitude defined by an inertial satellite system. The value of wake vortices rarefaction measured by an onboard air data system allows estimating the influence degree of wake vortices on the aircraft roll moment with the help of a special hardware and software complex and to determine the necessity to change the flight mode. It is proposed to use a missile bench for the dimensioning wake vortices on aircraft models in order to test computational methods of wake vortices dimensioning